DEVELOPMENT OF IDEAS ABOUT CIVIL SOCIETY IN THE WORKS OF WESTERN THINKERS - A.Utamuradov (Western European Studies, 2024)
The article analyzes the essence of the concept of civil society, the study of this concept by Western thinkers. The ideas of Cicero, Aristotle, representatives of Western New Age philosophy, Locke, Montesquieu, Rousseau, Hobbes, and Hegel were analyzed in the study of the concept of a prosperous society. Also, the theories of the most modern philosophers, such as Marx, Schumpeter, and Weber, were also studied
Keywords: civil society; society; state; person; laws